The wonder a novel - Donoghue, Emma 1969- (Picador, 2016)
An English nurse is brought to a small Irish village to observe what appears to be a miracle-a girl said to have survived without food for months-soon finds herself fighting to save the child's life. Tourists flock to the cabin of eleven-year-old Anna O'Donnell, who believes herself to be living off manna from heaven, and a journalist is sent to cover the sensation. Lib Wright, a veteran of Florence Nightingale's Crimean campaign, is hired to keep watch over the girl. Written with all the propulsive tension that made Room a huge bestseller, THE WONDER works beautifully on many levels--a tale of two strangers who transform each other's lives, a powerful psychological thriller, and a story of love pitted against evil
Keywords: Geschichte 1800-1900; Girls / Fiction; Fasting / Fiction; Nurses / Fiction; Large type books; Alltag, Brauchtum; Ireland / Social life and customs / 19th century / Fiction; Irland; Fiktionale Darstellung